The design of radiology viewing box using charger system and potentiometer - Diartama, Anak Agung Aris; Suswaty, Susy; Priantoro, Win; Sugiyanto; Sudiyono; Anwar, M. Choiroel; Latifah, Leny; Santjaka, Aris; Amri, Faisal; Mulyantoro, Donny Kristanto (GHMJ (Global Health Management Journal), 2017)
Background: In the process of work to gain the maximum results, a radiologist needs a viewing box tool to read radiographs. Therefore, the authors want to develop a viewing box tool, which in general the work if this tool resembles the factory manufactured tool. The viewing tool box made can adjust the intensity of the light produced. It uses batteries as a charger system, so that the viewing box can be used anywhere, especially areas that have not been reached by electricity.Aims: This study aimed to create a viewing box tool by using a potentiometer system and charger system.Methods: This study used applied research method by creating and using the design of viewing box tool by using a potentiometer and charger system. Using a Lux meter, the tool's feasibility and the quality of potentiometer system were assessed by 15 respondents consisting of five radiologists and 10 radiographers who should fulfill the questionnaire form.Results: The results of the questionnaire showed that 100% radiologist gave an A (excellent) and expressed that the viewing box tool created could be used properly and 90% radiographers provided an A (excellent) and expressed that the viewing box tool created could be used properly, while 10% radiographer gave a value of B (moderate).Conclusion: The proposed viewing box tool could be used properly and obtained optimal results as a tool in reading radiographs. Potentiometer system contained in the viewing box was very helpful in reading radiographs. Keywords: Viewing box, Radiology, Potentiometer, Charger Submitted: 3 May 2017, Accepted: 22 June 2017 DOI: https://doi.org/10.35898/ghmj-1196